EFFECT OF DOUBLE CHAMFER ON TESILE STRENGTH AND MICROSTRUCTURE OF AISI 304 FRICTION WELDING JOINTS - Penggalih, Bagus Samodra (Universitas Muhammadiyah Semarang, 2024)
Friction welding is a metal joining process without melting (solid state process), in which the welding process occurs as a result of combining the rotation rate of one of the workpieces with the compressive force exerted by the rotating workpiece. The friction caused by the meeting of the two workpieces will produce heat which can melt the two ends of the workpiece which are rubbing together so that they are able to melt and finally the joining process occurs. In this study, Continuous Drive Friction Welding (CDFW) was carried out on AISI 304 metal materials. This study aims to determine the effect of double chamfers on the tensile strength and microstructure of AISI 304 friction welding joints. The chamfer angle variations used are 15°, 30°, and 45°. The results of the tensile test show that chamfering can affect the results of the tensile strength. The highest tensile strength value was obtained at a chamfer angle of 30°, namely 454.9Mpa. Meanwhile, the lowest tensile strength value was obtained at the 45° chamfer angle variation, which was 193.5 MPa. The results of the microstructure test show that the chamfer angle has an effect on changes in the microstructure. At all variations of the chamfer angle, the microstructure of the weld area has perlite and ferrite fine grained phases, the HAZ region has perlite and ferrite phases larger and finer grained. Also found in all variations there is porosity. The greatest porosity is found at a chamfer angle of 45°.